Comparative Study of Oil and Gas Products with Manual Formula on a Laboratory Scale in Ensuring Production System Information - Haqi, Calista Aulia; Aulia Nuha, Maharani Pramesty; Zaydan, Mulki Maulana; Ryanthika, Nadira Annisa; Bayu Nugraha, Reo Samtalira; Verinza, Oksil (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2024)
This study explores the enhancement of oil and gas products through laboratory-scale manual formulations to address quality, efficiency, and environmental sustainability challenges. It focuses on biodiesel blends (B10, B30, and B50) and used lubricants treated with citric acid to reduce heavy metal content. The research identifies key functional components in biodiesel that improve combustion efficiency and lower greenhouse gas emissions. Simultaneously, the addition of citric acid in used lubricants aims to reduce metal concentrations, enhancing the potential for recycling and reuse. The results indicate that increasing biodiesel content significantly improves environmental performance and reduces reliance on fossil fuels, though water and sulfur content require strict monitoring to maintain product stability. In used lubricants, the application of citric acid demonstrates varied effectiveness, reducing specific metals like magnesium but increasing others such as calcium and zinc, posing challenges for consistent metal reduction. This study concludes that combining manual formulations and chemical treatments provides valuable insights into optimizing oil and gas products. It emphasizes the need for careful control of component levels to meet quality standards and environmental regulations. The findings suggest that refining the application of citric acid could further enhance its effectiveness in minimizing harmful metal concentrations, supporting sustainable and eco-friendly practices in the oil and gas sector.